INDONESIAN EFL STUDENTS’ PERCEPTION OF GOOGLE TRANSLATE UTILIZATION AS A TRANSLINGUAL TOOL IN WRITING CLASS - Azima, Rizki; Fithriani, Rahmah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2024)
This study aims to determine how students feel about utilizing Google Translate as a Translating tool when writing in EFL classes. Ten English education majors in their seventh semester participated in this phenomenological case study. data was collected from three participants who were specially chosen based on their responses to the online questionnaires, as well as an online questionnaire distributed to all participants. The data analysis showed that using Google Translate for EFL writing was favorably received. furthermore, they thought Google Translate was helpful since it helped them translate their writing and enhance their vocabulary. it appears that utilizing artificial intelligence (AI) in the form of online translation their written work. According to this study, incorporating AI-based technology into EFL writing will be beneficial in various ways. However, further research is needed to determine the relative impact of each element influencing students' use of AI-based translation tools, particularly Google Translate.